2019
DOI: 10.2319/051019-324.1
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between dental crowding and the size of the maxillary or mandibular apical base?

Abstract: Objective: To determine whether apical base size is related to dental crowding. Materials and Methods: Digital scans of dental casts were taken of 75 untreated Class I adults to measure maxillary and mandibular tooth size, dental arch perimeters, intermolar widths, and intercanine widths. Cone beam computed tomography (CBCT) images were used to measure the apical base of the maxilla and mandible, including the total cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
10
0
3
Order By: Relevance
“…An intense masticatory force induces the development of prominent bones and tooth grinding. Concerning the bones' size, recently it has been reported that the size of the maxillary basal bone is related to crowding for both upper and lower arches 29 . Therefore, Naia's maxillary width dimensions (Table 3 ) might explain crowding in the upper and even in the lower arch.…”
Section: Discussionmentioning
confidence: 99%
“…An intense masticatory force induces the development of prominent bones and tooth grinding. Concerning the bones' size, recently it has been reported that the size of the maxillary basal bone is related to crowding for both upper and lower arches 29 . Therefore, Naia's maxillary width dimensions (Table 3 ) might explain crowding in the upper and even in the lower arch.…”
Section: Discussionmentioning
confidence: 99%
“…Приріст їх розповсюдженості спостерігається у дітей в період змінного прикусу, який сягає 80% [1,2,4]. Причому, найчастіше зустрічаються аномалії I класу, які за даними різних авторів складають від 50,6% до 84,4%, а показник скупченості зубів у період змінного прикусу доходить до 77% [2,4,8]. Доведено також, що з віком скупченість зубів майже не піддається саморегуляції і в 80-90% випадків зі змінного прикусу переходить у постійний [3,5,7].…”
Section: вступunclassified
“…За даними вітчизняної та зарубіжної літератури розповсюдженість зубощелепних аномалій і деформацій у дітей та підлітків в період змінного прикусу досягає 80% (Alhammadi et al, 2018;Куроєдова, 2008;Дєньга, 2004). Найчастіше зустрічаються аномалії I класу, розповсюдженість яких, за даними різних авторів, складає від 50,6% до 84,4% (Crossley et al, 2020). Доведено також: з віком скупченість зубів майже не піддається саморегуляції і у 80-90% випадків зі змінного прикусу переходить у постійний (Ronay et al, 2008;Sayin & Türkkahraman, 2004).…”
Section: вступunclassified
“…Патологія скупченості зубів у змінному періоді прикусу є однією з найпоширеніших у практиці лікаря-стоматолога-ортодонта. Розповсюдженість її, за даними різних світових наукових джерел досягає 77% (Crossley et al, 2020;Куроєдова, 2008;Дєньга, 2004) і зустрічається на всі етапах формування зубощелепного апарату та є суттєвим ускладненням вже наявної патології прикусу.…”
Section: вступunclassified